Bistability-based foldable origami mechanical logic gates. (February 2021) - Meng, Zhiqiang; Chen, Weitong; Mei, Tie; Lai, Yuchen; Li, Yixiao; Chen, C.Q.
Abstract: Mechanical logic gates, counterparts of electronic logic gates, are highly desirable for the development of mechanical computing and robotic materials. Kirigami and origami based mechanical metamaterials have been shown to have attractive scale-free properties, e.g., multi-stability and programmability. Here, a bistability-based foldable waterbomb origami consisting of bistable kirigami units is proposed. The geometrical parameters dependence of the responses of the kirigami units and the origami is explored. Simplified models are developed, verified by numerical simulations and experiments. Based on the proposed origami, mechanical logic gates AND, OR, and NOT are designed and are experimentally demonstrated. The obtained results illustrate a possible solution for more complex logic operations (e.g., signal processing and data storage) from a mechanical deformation point of view by combining the logic gates together in a desired manner.